Risk of Early Bleeding with Dual Antiplatelet Therapy in Acute Stroke and Transient Ischemic Attack Regardless of NIHSS Admission. - Scavasine, Valeria Cristina (2021)
Background: Dual antiplatelet therapy (DAT) is a therapeutic option for patients with minor ischemic stroke (IS) or transient ischemic attack (TIA). No study has evaluated the incidence of early bleeding in patients with moderate to major ischemic stroke. The current study aimed to analyze both the frequency of early bleeding and hospital morbidity related to DAT for either acute IS or TIA regardless of admission National Institute of Health Stroke Scale (NIHSS) score. Methods: This was a retrospective analysis based on data collected from a prospective data bank of a single center. We included patients who underwent DAT in the first 24 hours of symptom onset with a loading dose (aspirin 300 mg + clopidogrel 300 mg) on the first day, followed by a maintenance dose (aspirin 100 mg + clopidogrel 75 mg). We analyzed intracranial and/or extracranial hemorrhage that had occurred during the hospital admission, symptomatic bleeding, modified Rankin Scale (mRS) score at discharge, and death rates as outcomes. Results: Of the 119 patients analyzed, 94 (79 %) had IS and 25 (21 %) had TIA. Hemorrhage occurred in 11 (9.2 %) and four (3.4 %) patients with TIA or NIHSS ≤ 3, respectively, although none were symptomatic. Patients with bleeding as a complication had higher admission NIHSS [4 (3–7) vs. 2 (1–4), p = 0.044] and had higher mRS at discharge (mRS 2 [1–5] vs. mRS 1 [0–2], p = 0.008). These findings did not indicate increased mortality, as one (9 %) patient died from bleeding and two (1.8 %) patients died without bleeding (p = 0.254). Conclusion: DAT seems to be a safe therapy in patients regardless of admission NIHSS if started within the first 24 h after symptom onset because only 1.6 % of patients had symptomatic bleeding.